2021
DOI: 10.3389/fneur.2021.620757
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence of Orthostatic Intolerance and Altered Cerebral Vascular Control Following Sport-Related Concussion

Abstract: Concussions have been shown to result in autonomic dysfunction and altered cerebral vascular function. We tested the hypothesis that concussed athletes (CA) would have altered cerebral vascular function during acute decreases and increases in blood pressure compared to healthy controls (HC). Ten CA (age: 20 ± 2 y, 7 females) and 10 HC (age: 21 ± 2 y, 6 females) completed 5 min of lower body negative pressure (LBNP; −40 mmHg) and 5 min of lower body positive pressure (LBPP; 20 mmHg). Protocols were randomized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…More pronounced reductions in PETCO 2 may have occurred during LBNP if we did not add CO 2 to the inspirate. We previously observed ∼5 mmHg decrease in PETCO 2 during 5 min of LBNP in healthy men and women ( Worley et al, 2021 ). Despite reductions in mean arterial pressure and PETCO 2 , MCAv was maintained throughout LBNP at pre- and post-BRJ ingestion ( Figure 5C ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…More pronounced reductions in PETCO 2 may have occurred during LBNP if we did not add CO 2 to the inspirate. We previously observed ∼5 mmHg decrease in PETCO 2 during 5 min of LBNP in healthy men and women ( Worley et al, 2021 ). Despite reductions in mean arterial pressure and PETCO 2 , MCAv was maintained throughout LBNP at pre- and post-BRJ ingestion ( Figure 5C ).…”
Section: Discussionmentioning
confidence: 90%
“…To attenuate reductions in PETCO 2 that can be observed during LBNP, participants inhaled a mild hypercapnic gas (FiCO 2 : 0.03, FiO 2 : 0.21, FiN 2 : 0.76) during baseline and throughout the duration of testing. Our lab has previously demonstrated that LBNP set to −40 mmHg for 5 min reduces PETCO 2 by 5 ± 3 mmHg in healthy, young adults ( Worley et al, 2021 ), which likely influences cerebrovascular responses to LBNP. However, elevated FiCO 2 can also impair CA.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, a randomised controlled trial found a ∆ HR cut-off metric (<50 bpm) to predict prolonged recovery 109. Pilot studies employing physiological stressors such as lower body negative and positive pressure110 and the Cold Pressure Test111 found group differences in cerebrovascular reactivity (CVR),110 HR and BP 111. One study found a significantly elevated Mayer wave proportion in the concussion group compared with control 112…”
Section: Resultsmentioning
confidence: 99%
“…58,59 The retention of MBP during the HUT in our final multivariable model supports prior studies suggesting abnormal sympathetic augmentation upon baroreceptor activation in people with post-mTBI dizziness. 6062 Given that prior studies have reported variable patterns of altered HR and BP control following mTBI, 34,63,64 and the preliminary nature of this study, future studies including HR and BP measures of cardiovascular autonomic function are needed. 37 In the meantime, these data support clinical (bedside) assessment of standard orthostatic vital signs 37,65 , which may provide an informative physiological correlate to symptoms of dizziness, provide an additional objective parameter to follow during rehabilitation, and direct treatment approaches.…”
Section: Discussionmentioning
confidence: 99%